Asymmetric leaflet tethering is associated with worse outcomes after edge-to-edge mitral valve repair for secondary mitral regurgitation. (14th October 2021) - Stolz, L; Orban, M; Braun, D; Doldi, P; Orban, M; Stocker, T; Mehr, M; Steffen, J; Loew, K; Hagl, C; Massberg, S; Naebauer, M; et al.
Abstract: Background: The impact of mitral valve (MV) tethering patterns on outcomes of patients undergoing transcatheter edge-to-edge mitral valve repair (TEER) for severe secondary mitral regurgitation (SMR) is unknown. Purpose: The purpose of this study was to evaluate the impact of asymmetric postero-anterior and medio-lateral MV leaflet tethering on procedural and survival outcomes after TEER for SMR. Methods: Symmetry of postero-anterior leaflet tethering was defined as the ratio of the posterior to anterior MV leaflet angle (PLA/ALA) in the central MV segment 2. The ratio of the tenting area between MV segments 3 and 1 (S3/S1 ratio) was defined as medio-lateral tethering symmetry. We used receiver operating characteristics and a proportional Cox model to identify cut-off values of asymmetric postero-anterior and medio-lateral tethering for prediction of two-year survival after TEER. Results: 178 patients receiving TEER for SMR were included. Asymmetric postero-anterior tethering was observed in 67 patients (37.6%, PLA/ALA ratio cut-off >1.54). Medio-lateral tethering was asymmetric in 49 patients (27.5%, S3/S1 ratio cut-off >1.49). MR was reduced to MR ≤2+ in 91.6% of patients, while postprocedural MR remained higher in the presence of asymmetric postero-anterior tethering (p=0.01). After adjustment for potential clinical and echocardiographic confounders, multivariable Cox regression analysis confirmed asymmetric postero-anterior tethering (HR=2.77, CI=1.43–5.38, p<0.01) and asymmetric medio-lateral tethering (HR=2.90, CI=1.54–5.45, p<0.01) as independent predictors for two-year survival. Conclusions: Asymmetric postero-anterior and medio-lateral MV leaflet tethering patterns independently increase two-year all-cause mortality in patients undergoing TEER for SMR. Detailed echocardiographic patient selection might improve outcomes after TEER. FUNDunding Acknowledgement: Type of funding sources: None.